Apuntes a Después de la teoría de Terry Eagleton (De la Crítica, 2020)
As soon as we read the title of Terry Eagleton's After Theory, we can feel the ironic and subversive language that this author uses to completely dismantle all the pre-established concepts that people have about what he calls high theory. In a precise way, it explains the process of degradation or systematic trivialization, to which intellectual production, and therefore culture, has been subjected. It highlights a complete detachment of the new generations from the old canons, to give way to the everyday or trivial, as the central axis of their productions, a trend that may have as its objective, to respond to the various cultural phenomena that have filled the stage. current social.